Peripheral nerve tumors - Purriel, Juan A (Cirugía del Uruguay, 1973)
On the basis of Del Río Hortega-Polak's classification of tumors of peripheral nerves, we only consider the two main types because of their frequency and topography: lemocytomas and lemocytofibromas. Lemocytomas (neurinomas, schwannomas or neurilemomas) are the most frequent in this series. Histogenesis in schwannic element is now recognized. They are single, circumscribed and well encapsuled tumors, with characteristic histology and fusiform elements arranged in intertwined fascicles showing typical "palisade" figures. Even though sorne authors describe malign forms, the majority hold they do not exist. Del Río Hortega recognizes a "sarcomatoid" form in vlhich nuclear pleomorphysm is evident and at odds with a markedly benign biology. Lemocytofibromas (neurofibromas) are rarer; isolated forros are exceptional, they are generally multiple and a part of v. Recklinghausen's neurofibromatosis. Histogenesis is mixed and originates in Schwann's cells and cells of fibroblastic component. They are benign, encapsuled, and its histology showing their double origin. Malign forms described are exclusively derived from fibroblastic element; their behaviour is that of any fibrosarcoma of other origin.